Beyond Sociology Trans-Civilizational Dialogues and Planetary Conversations (Springer Singapore, 2018)
This book explores the contours of a transformational sociology which seeks to reconsider the horizons of sociological imagination. It questions accepted modernist assumptions such as the equation of society and nation-state, the dualism of individual and society and that of ontology and epistemology. Arguing that contemporary sociology suffers from what Ulrich Beck calls the Nato-like fire power of western sociology, it argues that sociology has to open itself to transcivilizational dialogues and planetary conversations about self, culture and society. The book also challenges scholars to go beyond a privileging of the post-traditional telos of modernist sociology and puts forward a foundational interrogation of modernist sociology. It underscores the limitations of established conventions of sociology and considering an alternative sociology based upon Confucian vision and practice of self-transformation. This collection offers a way to go beyond dominant structures of modern sociology and contemporary dominant ways of thinking about and doing sociology helping us cultivate a transdisciplinary sociology.